The Implementation of Qur’anic Values in the Management of Modern Pesantren in Indonesia - Rahman; M. Hidayat Gynanjar; Moch.Yasykur (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study explores how Qur'anic values are integrated into the management of modern pesantren. (Islamic boarding schools) through a literature review approach. It draws upon primary sources such as the Qur'an and classical Islamic texts that serve as foundational references in Islamic education. The analysis focuses on three main aspects: Qur'an-based planning, spiritual leadership, and institutional governance. Qur'an-based planning emphasizes the importance of a pesantren’s vision and mission, rooted in the principles of ihsan (excellence) and tawakkal (trust in God). Spiritual leadership highlights the role of kiai and pesantren administrators in fostering exemplary conduct, honesty, and noble character as the cornerstone of organizational culture. Meanwhile, institutional governance encompasses administrative systems, curriculum development, and social relations within the pesantren, guided by the principles of musyawarah (deliberation), amanah (trustworthiness), and justice. The findings suggest that integrating Qur'anic values into modern pesantren management, as reflected in classical Islamic sources, contributes to both character development among students and the overall effectiveness of pesantren governance.